2017
DOI: 10.1007/s40801-017-0120-y
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Hip Fracture Due to Mirtazapine Exposure When Switching Antidepressants or Using Other Antidepressants as Add-On Therapy

Abstract: BackgroundAntidepressants are associated with adverse effects such as sedation and hypotension, which can result in falls and fractures. Few studies have assessed the risk of hip fracture due to mirtazapine, and no known studies have assessed whether the risk of hip fracture is higher in patients taking other antidepressant medicines in combination with mirtazapine.ObjectivesThis study aimed to examine the risk of hip fracture in older people due to mirtazapine use as well as switching between or concurrently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Particularly, the results showed that zopiclone was frequently co‐prescribed with other drugs prior to a fracture event. Several studies have shown that z hypnotics significantly increase the risk of fracture in older adults, and our results are biologically plausible …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Particularly, the results showed that zopiclone was frequently co‐prescribed with other drugs prior to a fracture event. Several studies have shown that z hypnotics significantly increase the risk of fracture in older adults, and our results are biologically plausible …”
Section: Discussionsupporting
confidence: 75%
“…Several studies have shown that z hypnotics significantly increase the risk of fracture in older adults, and our results are biologically plausible. [30][31][32][33][34] The sensitivity analyses repeated with weekly (7-day) and monthly (30-day) time windows did not change the overall results. These time windows were chosen to align with the best practice recommendations for conducting a case-crossover study.…”
Section: Discussionmentioning
confidence: 85%
“…While a meta-analysis of case-control and cohort studies suggests an association between TCAs and hip fracture, this relationship has not been previously assessed in any other case-crossover study controlling for patient-specific, time-invariant confounders [ 15 ]. In line with Maclure and Mittleman’s recommendation [ 6 ] to conduct a case-control study as a type of validation for a case-crossover study, our case-control study conducted in the same setting found that new use of TCAs was not independently associated with hip fracture [ 16 ]. The conservative use of TCAs at low doses to treat neuropathic pain or depression in older people could partly explain the lack of association in our case-crossover and case-control studies [ 7 ].…”
Section: Discussionmentioning
confidence: 79%
“…We applied an active comparator new user design, 34 comparing the risk of persons initiating a certain AD to the risk of persons initiating mirtazapine (active comparator) which is frequently used and has been associated with a low risk of hip fractures. 35 To be eligible, persons had to be older than 65 years and have at least 12 months of continuous enrollment before cohort entry. Patients entered the cohort at the date of the first AD dispensation after 365 days without such a dispensation ("initiation").…”
Section: Methodsmentioning
confidence: 99%